THE INFLUENCE OF DIGITAL MARKETING ON ISLAMIC FASHION CONSUMPTION: INVESTIGATING MILLENNIALS’ PURCHASE INTENTION IN DIGITAL INFLUENCERS (International Journal of Islamic Business, 2025)
This study investigates how millennials’ fashion purchase behaviors are influenced by digital influencers, focusing on key factors such as perceived credibility, expertise, congruence, attractiveness, and para-social interaction. While influencer marketing is a major component of digital marketing, there remains a lack of tailored strategies targeting millennials, the primary demographic for social media engagement. A quantitative research approach was employed, utilizing an online survey distributed to 307 millennial social media users to analyze the extent to which digital influencers impact their purchasing decisions. Findings reveal that perceived credibility, congruence, attractiveness, and para-social interaction significantly influence millennials’ purchase intentions, whereas perceived expertise does not exhibit a significant effect. However, the study is limited to a millennial sample, and the findings may not be generalizable to other demographic segments. Future research should explore how these influencer-related factors impact different consumer groups to develop a comprehensive understanding of digital marketing effectiveness. The study provides valuable insights for fashion brands seeking to optimize their digital engagement strategies, emphasizing the importance of credibility, authenticity, and interaction-driven influencer marketing to strengthen brand-consumer relationships. By deepening the understanding of influencer marketing strategies in the fashion industry, this research offers practical recommendations for brands aiming to enhance their influence on millennial purchasing behavior in the digital age.